Evaluación de la producción de hidrógeno a partir de electrólisis de agua de mar utilizando energía renovable como fuente de energía eléctrica. (2021)
In the following work, an evaluation of hydrogen production from seawater electrolysis using renewable energy as a source of electrical energy was developed. In the first place, the entire bibliographic review regarding the production of hydrogen in the world was developed and in Colombia, following this, the different forms of hydrogen production were identified. Continuing the bibliographic review, this review focused on the different renewable forms of hydrogen production and which of these have been or can be used in the country. With this in mind and looking for different ways of producing hydrogen, the decision is made to use wind energy as a source of electrical energy that provides the energy necessary to obtain hydrogen due to the geographical properties of the country.